Decreased cholesterol levels reflect a consumption of anti-inflammatory isoprenoids associated with an impaired control of inflammation in a mouse model of mevalonate kinase deficiency. - Marcuzzi, Annalisa; Decorti, Giuliana; Pontillo, Alessandra; Ventura, Alessandro; Tommasini, Alberto (Inflamm Res, 2010)
OBJECTIVE: The aim of this study was to evaluate, in a mouse model of mevalonate kinase deficiency (MKD), the possible link between inflammatory symptoms and serum cholesterol levels. MATERIALS AND METHODS: Balb/c mice were treated with alendronate and bacterial muramyl dipeptide. Body temperature, interleukin-1 beta (IL-1 beta) secretion and serum cholesterol levels were measured. RESULTS: An increased production of the pro-inflammatory cytokine IL-1 beta (p < 0.05) and a rise in body temperature (p < 0.05) was observed, while, in parallel, serum cholesterol concentration significantly decreased (p < 0.05). These effects were completely reversed when animals were treated with exogenous isoprenoids. CONCLUSIONS: In the mouse model of MKD, the inflammatory response is associated with a reduction in cholesterol levels, and hence this parameter could be used as an indicator of isoprenoid consumption. In addition, plant derived isoprenoids could represent candidate treatments for this disease.
Keywords: Animals; Anti-Inflammatory Agents; Cholesterol; Disease Models, Animal; Inflammation; Interleukin-1beta; Male; Mevalonate Kinase Deficiency; Mice; Mice, Inbred BALB C; Random Allocation; Terpenes